Pengaruh Pelatihan Karyawan, Lingkungan Kerja, Dan Komitmen Perusahaan Terhadap Kinerja Karyawan Di PT. Milagros Indonesia Megah - Mariyatul Qibliyah; Parwita Setya Wardhani; Ec Sofyan Lazuardi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to determine whether employee training, work environment and company commitment to employee performance at PT. Milagros Indonesia Megah. This type of research is quantitative. The population studied in this study were all employees at PT. Milagros Indonesia Megah. The number of samples in this study was 55 respondents. The sample collection technique in this study was carried out by probability sampling. The data collection technique used in this study was a questionnaire distributed to all employees of PT. Milagros Indonesia Megah. The data analysis technique used in this study was multiple linear regression analysis using SPSS (statistical Product and Services Solution) software version 29.0. The results of the study indicate that employee training variables have a positive and significant effect on employee performance with a t-count value = 7.570 > t-table 2.007, work environment variables have a positive and significant effect on employee performance with a t-count value = 5.214 > t-table 2.007, and company commitment variables have a positive and significant effect on employee performance with a t-count value of 3.410 > t-table 2.007. From the three results, it shows that employee training, work environment and company commitment to employee performance have a partial effect. For simultaneous testing, the results obtained that all variables together have a significant effect on employee performance.